Isolation and characterization of Iwanai Valley virus, a new tick-borne nairovirus from Ixodes ovatus ticks in Hokkaido, Japan - Matsumura, Ryo; Kobayashi, Daisuke; Yamauchi, Takeo; Park, Eunsil; Nishino, Ayano; Maeda, Ken; Kasai, Shinji; Itoyama, Kyo; Isawa, Haruhiko (Archives of virology, 2025)
Most members of the genus Orthonairovirus, represented by Crimean-Congo hemorrhagic fever virus and Nairobi sheep disease virus, are tick-borne, and some have become a public health concern in recent years. Here, we report the isolation and genetic and biological characterization of a new orthonairovirus, designated as "Iwanai Valley virus" (IWVV), from Ixodes ovatus ticks in Hokkaido, Japan. The amino acid sequence of the viral nucleoprotein (NP) was found to be 34-45% identical to those of known orthonairoviruses. Phylogenetic analysis based on amino acid sequences of the viral NP revealed that IWVV is closely related to human-pathogenic tick-borne orthonairoviruses, including Songling virus, Tacheng tick virus 1, and Yezo virus, which were recently discovered in East Asia. BHK-21 (Syrian hamster kidney), Vero (African green monkey kidney), SW-13 (human adrenal adenocarcinoma), HuH-7 (human hepatocellular carcinoma), and ISE6 (Ixodes scapularis tick embryo) cells were found to be susceptible to IWVV infection. Notably, several human-derived cell lines supported efficient replication of the virus. Our findings provide new insights into the diversity, evolutionary dynamics, and geographical distribution of orthonairoviruses in East Asia.